2017
DOI: 10.1111/acem.13068
|View full text |Cite
|
Sign up to set email alerts
|

Initial Validity Analysis of the American Board of Emergency Medicine Enhanced Oral Examination

Abstract: Objectives: The American Board of Emergency Medicine (ABEM) has introduced a new testing format for the oral certification examination (OCE): the enhanced oral or "eOral" format. The purpose of this study was to perform initial validity analyses of the eOral format. The two hypotheses were: 1) the case content in the eOral format was sufficiently similar to clinical practice and 2) the eOral case materials were sufficiently similar to clinical practice. The eOral and traditional formats were compared for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Prior studies of the in-person OCE showed substantial validity and reliability support. [4][5][6][7][8] To maintain a similarly high level of validity and reliability, ABEM designed the VOE to be similar to the OCE in content and administration. The OCE had amassed substantial validity evidence as previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies of the in-person OCE showed substantial validity and reliability support. [4][5][6][7][8] To maintain a similarly high level of validity and reliability, ABEM designed the VOE to be similar to the OCE in content and administration. The OCE had amassed substantial validity evidence as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first report of validity and reliability evidence for the virtual format of the ABEM certifying examination. Prior studies of the in‐person OCE showed substantial validity and reliability support 4–8 . To maintain a similarly high level of validity and reliability, ABEM designed the VOE to be similar to the OCE in content and administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The examination has been studied thoroughly and has been found to have sufficient validity evidence and reliability support to make summative certification decisions. [13][14][15][16][17][18] During the COVID-19 pandemic, ABEM converted the administration of the OCE to a virtual platform. OCE results from the virtual oral examination format are excluded from this investigation.…”
Section: The Bottom Linementioning
confidence: 99%